PEMANFAATAN MIKORIZA ARBUSKULA SPESIFIK LOKASI UNTUK EFISIENSI PEMUPUKAN PADA TANAMAN JAGUNG DI LAHAN GAMBUT TROPIS - Iwan Sasli; Agus Ruliansyah (Agrovigor, 2012)
This research aims to explore the origin of mycorrhizal spores associated mutually in peat soil with some plant rhizosphere. This research was conducted to study the effectiveness of Mycorrhizae and inorganic fertilizers on growth and yield of corn in peat soil. The experiment was conducted on peat lands in North Pontianak, West Kalimantan. Mycorrhizal factors consist of the level: without mycorrhizae, rhizosphere of mycorrhizal pineapple origin, pineapple root extract, and mycofer, as the main plot. The doses of inorganic fertilizer (N, P, K, Mg) as the subplot consisted of: no inorganic fertilizers, half dose of inorganic fertilizer, and full recommended dose as a subplot. The research variables measured were plant height, fresh weight of corn, the dry weight of 100 grains of corn, root dry weight, and nutrient uptake (N, P, K, Mg). The results showed that the spores of mycorrhizal rhizosphere of several plants in peat soils can be applied to plants. Applications of Western Kalimantan peat land Mycorrhizal can improve plant growth and increase the uptake of N, P, K, Mg on corn. Best plant growth resulting from mycorrhizal of pineapple root extract. Uptake of the highest N, P, K, Mg, produced by treatment of mycorrhizal from pineapple root extract with half the recommended dose of inorganic fertilizer.